Evaluation of Metropolitan Municipalities Web Sites in terms of Governance Principles - GENÇKAYA, ÖMER FARUK (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2021)
Local governments publicize information such as the agenda of local councils, minutes of council meetings, their annual budgets, the strategic plans, and the other essential documents on their official websites. This study aims to assess the official websites of local governments, which are the closest service units to the citizens, in terms of governance principles such as openness, transparency, and participation. The web pages of thirty metropolitan municipalities were evaluated in terms of competence with the Stapel scale and content analysis method according to the thirteen main criteria. The method of LBWA in weighting the criteria and CoCoSo method in the ranking of websites were used. The findings indicate that metropolitan municipality websites do not have sufficient levels in terms of transparency, audit, and accountability.
Keywords: Governance; Web Pages of Metropolitan Municipalities; LBWA; CoCoSo; E-GOVERNMENT; PUBLIC VALUE; TRANSPARENCY; INFORMATION; ACCOUNTABILITY; CITY; EVOLUTION; ICTS; EU